Optimalisasi Penginputan Bahan Pustaka Berbasis Teknologi Informasi di Perpustakaan STMIK AMIK Riau - Yasin Setiawan (Jurnal Gema Pustakawan, 2022)
The STMIK-AMIK Riau Library is a library that is present in the academic environment in the field of information technology. The rationale is that these universities have a great opportunity to maximize information technology in processing library materials. However, in the field there are serious obstacles in the form of non-optimal processing of library materials due to the slow working computer used. The research aims to optimize the process of inputting library materials with existing devices. The methodology used is SDLC (System Development Life Cycle) including system analysis, optimization design, implementation and evaluation. There are four optimization strategies tested in this study, which aim to improve computer performance for processing library materials. The results showed that the optimization succeeded in increasing the efficiency of work computers by 57%. The test results for inputting library materials show an efficiency of 43%. The waiting time for processing five book samples, which was originally 1,098 seconds (18.3 minutes), became 650 seconds (10.4 minutes). The conclusions of the study indicate that the collection of library materials has accelerated the process and is more effective after optimization strategies have been carried out on computer devices.